Parotid Gland Oncocytoma and Its Clinicopathological Approach: A Case Report - Dewi, I Gusti Ayu Sri Mahendra; Sudarsa, I Wayan; Mahastuti, Ni Made; Patriawan, Putu; Paskarani, Putu Erika; Heryanto, Budi (Indonesian Journal of Cancer, 2025)
Introduction: Oncocytoma is a benign tumor of the salivary glands consisting of oncocyte cells, occurring in approximately 2% of all salivary gland neoplasms, most of which occur in the parotid gland. This tumour most commonly occurs in the sixth to eighth decades of life, with a mean age of 64 years and without gender predilection. The clinical presentation is often misdiagnosed as pleomorphic adenoma, cystic lesion, and inflammation.Case Presentation: A 63-year-old male, complained of a lump under the right ear, for 7 years ago. It feels painless and slightly enlarged since a month before surgery. Based on clinical examination suspected as benign cystic lesion due to inflammation and ultrasound suggesting a benign tumour mass with multiple lymphadenopathies at the right and left submandibular and right parotid. Then, the resected tumour continued for histopathological examination. Microscopically, the tumor cells are confined to the tissue. It consists of a uniform large polygonal cell with granular eosinophilic cytoplasm without any mitosis and necrotic area.Conclusions: Oncocytoma is a rare benign tumor of the salivary glands, especially affecting the parotid gland. Clinical and radiologically it is often misdiagnosed, so histopathological examination is needed for diagnostic confirmation for the best patient outcomes